Motivation on Boba Drink Consumption - Nadia Ulfa Nashwara; Cita Eri Ayuningtyas (Universitas Tanjungpura, 2022)
Boba drinks are popular in the trend of sweet foods and drinks in great demand by millennials. According to previous research, the sugar content in this boba drink is very high and is included in the category of high-sugar drinks that can cause serious health effects if consumed in excess. This study aims to determine the motivational factors for the consumption of boba drinks by people in the city of Yogyakarta. This research was qualitative research with a phenomenological approach. The study was conducted at boba beverage outlets in Yogyakarta by using purposive sampling. Respondents who participated in this study were 5 people who had consumed boba drinks at least once in the past month. Data collection was carried out by in-depth interviews with respondents, and data triangulation was carried out to ensure that the data obtained were valid. The results showed that the respondents liked the creamy and sweet taste. The distinctive taste of boba drinks was the main attraction for consumers. In addition, at price, respondents felt that the price and the product served were appropriate. Brand popularity also affected respondents' motivation to try the drink, based on drink advertisements that include promos. Price was a factor of consideration because consumers would see the suitability of the price with the goods purchased. Conclusion: motivation to consume boba drinks is motivated by various factors, including taste, price, brand, atmosphere, and promotion.